Marie Duval : maverick Victorian cartoonist - Grennan, Simon; Sabin, Roger, 1961-; Waite, Julian (Manchester : Manchester University Press, 2020)
Marie Duval: maverick Victorian cartoonist offers the first critical appraisal of the work of Marie Duval 1847-1890), one of the most unusual, pioneering and visionary cartoonists of the later nineteenth century, focusing on new types of cultural work by women and establishing Duval as a unique but exemplary figure in a transformational period of the nineteenth century.
Appendix 1: Questions of attribution -- Appendix 2: Questions of terminology and historicisation -- Bibliography -- Index
Print version record.
Includes bibliographical references and index.
JSTOR
Keywords: De Tessier, Isabelle Émilie, -- 1847-1890 -- Criticism and interpretation; De Tessier, Isabelle Émilie, -- 1847-1890 -- Criticism and interpretation; Caricatures and cartoons -- Great Britain -- History -- 19th century; Electronic books; Caricatures et dessins humoristiques -- Grande-Bretagne -- Histoire -- 19e siècle.; Livres numériques.; e-books.; LITERARY CRITICISM / General; Caricatures and cartoons; Great Britain; 1800-1899; Electronic books; History; Criticism, interpretation, etc